Complexity-Based Economic Growth: Integrating Productivity, Industrial Structure, and National Competitiveness - Zaini, Moh (PT. Anagata Sembagi Education, 2026)
Economic growth is increasingly understood as a complexity-based process that integrates productivity, industrial structure, and national competitiveness within a unified system. This study aims to analyze how complexity-driven economic growth emerges through the interaction of these key dimensions. The research employs a qualitative approach with a descriptive-analytical design using a literature-based method. Data were collected from reputable scholarly journals and international reports and analyzed using content and thematic analysis to identify patterns related to economic complexity, productivity dynamics, and structural transformation. The findings reveal that economic complexity significantly enhances productivity by fostering diversified, interconnected, and knowledge-intensive industrial structures. Structural transformation from low-productivity sectors to advanced manufacturing and services plays a crucial role in increasing total factor productivity and strengthening global competitiveness. In addition, innovation, institutional quality, and industrial linkages are identified as key drivers of sustainable growth. However, challenges such as limited technological capacity, structural rigidity, and policy misalignment remain critical, particularly in developing economies. The discussion highlights the importance of integrated and capability-based industrial strategies to overcome these constraints. In conclusion, complexity-based economic growth provides a comprehensive framework for achieving sustainable and competitive development when supported by innovation, institutional strength, and strategic policy alignment.